EFEKTIFITAS MEDIA BEJUBEL PADA MATERI JUAL BELI DI KELAS IV SD NEGERI 239 PALEMBANG - Yolanda, Prita Amelia; Rodiyah, Afifah Lisaiha; Purnama, Vivi Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the interactive slide-based learning media "BEJUBEL" (Belajar Jual Beli), which incorporates South Sumatera’s local wisdom, in improving the learning achievement of IVth grade students on buying and selling material at SD Negeri 239 Palembang. BEJUBEL is designed to enhance students' interest, motivation, and understanding of buying and selling topics that are closely related to everyday economic activities. The method used is a quantitative descriptive approach with a quasi-experimental design. Class IV.A as the control group, received conventional instruction without any specialized media, while Class IV.B, as the experimental group, used BEJUBEL media within a cooperative learning model. Data were collected through pretests and posttests in the form of multiple-choice questions. Data analysis was conducted using the t-test after normality and homogeneity tests were met. The study results show a significant difference in learning improvement between the experimental and control groups (p < 0.05), with students in the experimental group experiencing greater learning gains than those in the control group. The findings indicate that BEJUBEL media effectively enhances students' achievement and understanding of the buying and selling material. It can also serve as a valuable reference for teachers in developing technology-based learning media to improve the quality of education.